Pemanfaatan Lahan Kosong dan Peremajaan Lingkungan untuk Mengantisipasi Musim Hujan - Gilang; Prayitno, Muhammad Irfan; Advent; Wahyu; Ihsan; Hedi, Tubagus (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
Real Work Lecture (KKN) activities are an integral part of the higher education curriculum in Indonesia, including at the Faculty of Engineering. KKN aims to develop students' abilities to apply science and technology to solve problems in society. This articlediscusses the implementation of KKN in the Faculty of Engineering, focusing on the role of students in developing local infrastructure, community welfare, and environmental management. Through involvement in construction, design, and infrastructure maintenance projects, students learn to collaborate with communities, improve technical skills, and understand the social impact of engineering projects. The emphasis on problem-based learning and community service also helps shape students' social awarenessand responsibility as future engineers. The results of KKN at the Faculty of Engineering make a significant contribution not only toacademic development, but also to sustainable development and improving the quality of life in various regions of Indonesia.